Sustainability of Fish Fillet Processing Industries in Batang District - Astrid Fauzia Dewinta; Widodo Farid Ma'ruf (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightsSustainability index from fish fillet industry is important to know because a fishing industry just not looking for feasibility study in economic dimension but all dimension (resources, technology, social, legal and institutional)Multidimension sustainability index from fish fillet processing industry in Batang is included in the category of